Optimalisasi Pekerjaan Jembatan Utama Proyek Lanjutan Aksesibilitas Bandara Soekarno Hatta PT Wijaya Karya di Masa Pandemi Covid-19 Tahun 2020-2021 - Jessica Clarista Ismiarso; Novenda Kartika Putrianto (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2021)
This study examines the delayed development of the Soekarno Hatta-Tangerang Airport Accessibility project due to the Covid-19 pandemic, particularly in the construction of the main bridge. To address the delay, work optimization was carried out using the Critical Path Method (CPM) and project crashing method. Two optimization alternatives were identified: increasing working hours (overtime) and shift work. The research results show that both alternatives can perform crashing in 118 weeks, but there is a difference in direct cost. By using the alternative of increasing working hours, there is an additional cost of Rp 1,455,346,223.78, while by using the shift work alternative, the additional cost is Rp 1,562,626,223.78. The value of indirect cost is the same because the crashing duration is the same, and the direct cost increases because the crashing calculation is based on time and workers on the ground. Therefore, optimizing the main bridge construction work by increasing working hours is the alternative that suits the owner's request because the cost and duration calculations are in line with the owner's request. The findings of this study can help other construction projects facing similar challenges caused by the pandemic to determine the most appropriate optimization alternative. Keywords